1978
DOI: 10.1007/bf00267604
|View full text |Cite
|
Sign up to set email alerts
|

Chloramphenicol resistance in Streptomyces coelicolor A3(2): Possible involvement of a transposable element

Abstract: The transfer of a Chl element, causing resistance to chloramphenicol in Streptomyces coelicolor A3(2), was studied in NF x SCP1- superfertile crosses. When the Chl element is on the donor side (NF) its transfer to the recombinant cells was virtually total as if the element acted as a second concomitant transfer origin. When the Chl element was on the recipient side (SCP1-) it was never displaced by the immigrant chromosome even when the region facing chl+ was selected for. A fraction of the original Chl- mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1980
1980
1987
1987

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Previous attempts to genetically map the Camr determinant and argG genes in S. coelicolor A3(2) revealed ambiguities (10,35,36). We believed that the presence in the genome of one parental type of large DNA deletions and amplified DNA sequences could drastically affect segregation patterns, giving rise to ill-defined map positions.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Previous attempts to genetically map the Camr determinant and argG genes in S. coelicolor A3(2) revealed ambiguities (10,35,36). We believed that the presence in the genome of one parental type of large DNA deletions and amplified DNA sequences could drastically affect segregation patterns, giving rise to ill-defined map positions.…”
Section: Discussionmentioning
confidence: 96%
“…(19,26,27,30,36), although they are not correlated with amplification of DNA sequences. For S. cattleya, the gene for argininosuccinate synthase, argG, has been cloned and used to demonstrate that the Arg phenotype in variant strains results from deletion of this gene (26,39).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…References: (1) Rcdshuw et ell. (1979); (2) Matsubara-Nakano1 Kataoka and Oga\vara (1980); (3) Sermonti et of. (1978); (4) Nakano, Ozawa and Ogcl\v<ua (1980); (5) Altcnbuchncr and Cullum (1984); (6) lshiharn.…”
Section: Instabilitiesmentioning
confidence: 99%
“…Sermonti et al, (1977) interpreted emIR x Cml s matings as showing evidence of high-frequency transfer of the emiR gene independently of chromosomal gene transfer and concluded that the eml R gene \vas carried on an extrachromosomal element; however~Freeman~Bibb and Hopwood (1977) showed that the emIR gene was not carried on any known extrachromosomal element in S. coelicolor. It was subsequently suggested that the CmP~gene was on a transposable element that transposed between different chromosomal locations at such a high frequency that any population of cells contained individuals with the emIR gene at different locations, thus confounding normal mapping procedures (Sermonti et al, 1978;SermontiL anfaloni and Micheli, 1980). These authors tried to overcome this problem by splitting transconjugants into different classes where each class should be derived from parents with the emIR in a different particular location.…”
Section: Chloramphenicol Resistance and Arginine Ins1'abili1"ies In Smentioning
confidence: 99%